2013
DOI: 10.1111/jscm.12007
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Managers' Perceived Bias in Supplier‐Selected Referrals

Abstract: In evaluating suppliers in complex purchasing decisions involving customized solutions, purchasing managers must judge the capabilities suppliers have to provide the solutions, a judgment that often includes considerable uncertainty. To reduce this uncertainty, suppliers often ask their existing customers to be reference customers and give a referral to purchasing managers — that is, suppliers and purchasing managers consider a supplier‐selected referral as a source of information. However, in contrast to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…However, a more strategic perspective on the firm's key accounts might give greater consideration to the opportunities for future investment and long-term business development (McGinnis & McCarty, 1998;Zupancic, 2008). Some suppliers might attach greater importance to the reputational benefits associated with customers who boost their credibility and allow them to tout their competence (Hada et al, 2013). Others might cherish customers who have a particular interest in innovation, providing distinct opportunities and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 p p l y C h a i n M a n a g e m e n t : a n I n t e r n a t i o n a l J o u r n a l 11 incentives to differentiate themselves from their competitors (Capaldo, 2007;Soosay, Hyland, & Ferrer, 2008).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…However, a more strategic perspective on the firm's key accounts might give greater consideration to the opportunities for future investment and long-term business development (McGinnis & McCarty, 1998;Zupancic, 2008). Some suppliers might attach greater importance to the reputational benefits associated with customers who boost their credibility and allow them to tout their competence (Hada et al, 2013). Others might cherish customers who have a particular interest in innovation, providing distinct opportunities and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 p p l y C h a i n M a n a g e m e n t : a n I n t e r n a t i o n a l J o u r n a l 11 incentives to differentiate themselves from their competitors (Capaldo, 2007;Soosay, Hyland, & Ferrer, 2008).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Whyte (2003) studied how different users in different contexts within building construction in the UK and US have diverse requirements that demand tailored solutions. Suppliers might select an existing or previous client or user as a reference for a purchasing organization (Hada et al 2013). Users can influence purchasing decisions in a positive way by suggesting the need for certain materials and by defining standards of product quality or, in a negative way, by refusing some products.…”
Section: Active Rolesmentioning
confidence: 99%
“…Elaborate review of literature in multi‐sourcing procurement can also be found in the related literature (Balakrishnan and Natarajan , Hada et al. , Heide et al. , Honhon et al.…”
Section: Introductionmentioning
confidence: 99%